Innovation, Sustainability, Development: A New Manifesto - STEPS Centre (STEPS Centre, 2010)
Our Manifesto project publication is available in print, on CD or to view online. Innovation, Sustainability, Development: A New Manifesto recommends new ways of linking science and innovation to development for a more sustainable, equitable and resilient future. The multimedia version, with added audio, video and background documents, is available on CD and online.